Penerapan PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN TENTANG SIKLUS HIDUP HEWAN UNTUK MENINGKATKAN HASIL BELAJAR DI KELAS III UPTD SDN BALFAI - Venansius Titen; Antonius Suban Hali; Benu, Adam Bol Nifu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ learning outcomes through the implementation of the Problem Based Learning (PBL) model in science and social studies (IPAS) learning on the topic of animal life cycles in Class III C at UPTD SD Negeri Balfai. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. The research subjects were 20 students, consisting of 6 boys and 14 girls. Data were collected through observation and learning outcome tests, then analyzed using descriptive quantitative methods based on average scores and the percentage of learning mastery. The results showed that the implementation of the PBL model gradually improved students’ learning outcomes. The average score increased from 67.05 in the pretest to 71.75 in Cycle I and further increased to 85.5 in Cycle II. The percentage of learning mastery also improved from 45% in the initial stage to 60% in Cycle I and reached 90% in Cycle II. In addition, students’ learning activities improved from the fair category to the very good category. Therefore, the implementation of the Problem Based Learning model proved effective in improving IPAS learning outcomes on the topic of animal life cycles in Class III C at UPTD SD Negeri Balfai.